Exploring Relation between Indian Market Sentiments and Stock Market Returns - Aggarwal , Divya (Asian Journal of Empirical Research, 2017)
This paper aims to understand the relation between contemporaneous stock market returns and investor sentiments in Indian context. The analysis is done for daily data over a range of five years. Market measure proxies of investor sentiments including the market mood index and the volatility index are examined to explore their nature of association with the stock market returns. The results show that changes in sentiments have a higher explanatory power than sentiments at level when determining statistically significant relation with stock market returns. While the market mood index indicating optimism is positively related with stock returns, the VIX index also referred to as the fear guard index has a negative relation with stock returns. Moreover the market mood index seems to granger cause stock market returns and exhibit a long run association with stock market returns. With presence of sentiments impacting stock market returns established, more studies in context of developing countries are needed to understand the temporal dynamics between sentiments and stock markets.